Cytotoxicity, DNA binding and cell apoptosis induction of a zinc(ii) complex of HBrQ. Issue 12 (30th November 2015) - Zhang, Hai-Rong; Liu, Yan-Cheng; Meng, Ting; Qin, Qi-Pin; Tang, Shang-Feng; Chen, Zhen-Feng; Zou, Bi-Qun; Liu, You-Nian; Liang, Hong
Abstract : A zinc(ii ) complex of HBrQ showed higher in vitro antitumor activity. It induced cell apoptosis in BEL-7404 cells via G2 phase arrest, led to mitochondria dysfunction and activation of caspase cascade. The central zinc(ii ) should play a key role to enhance the antitumor effect Abstract : A new zinc(ii ) complex (1 ) of 5-bromo-8-hydroxyquinoline (HBrQ) was prepared and structurally characterized using IR, ESI-MS, elemental analysis, 1 H and 13 C NMR, as well as single crystal X-ray diffraction analysis. The DNA binding study on complex1, which was performed using UV-vis, fluorescence and circular dichroism (CD) spectral analyses, suggested that complex1 interacts with ct-DNA mainly via an intercalative binding mode. The in vitro cytotoxicity of complex1, compared with Zn(OAc)2 ·H2 O, HBrQ and cisplatin, was screened against a series of tumor cell lines as well as the normal liver cell line HL-7702 using the MTT assay. Complex1 showed much higher cytotoxicity than Zn(OAc)2 ·H2 O and HBrQ against most of the tumor cell lines, in which BEL-7404 was the most sensitive tumor cell line towards1, with an IC50 value of 8.69 ± 0.04 μM. Complex1 was found to greatly induce cell cycle arrest in the BEL-7404 cells at the G2 phase, and consequently to induce cell apoptosis in a dose-dependent mode, which is suggested by the cell apoptosis analysis via the Hoechst 33258 and AO/EB staining assays. Targeting the mitochondria pathway due to the redox activity of Zn, the apoptotic mechanism in the BEL-7404 cells treated by1 was investigated using reactive oxygen species (ROS) detection, intracellular calcium concentration measurement and caspase-9/3 activity assay, which showed that the cell apoptosis induced by1 was closely related to the loss of mitochondrial membrane potential, ROS production and enhancement of intracellular [Ca 2+ ], which trigger caspase-9/3 activation via the mitochondrial dysfunction pathway.